The Effect of Conscientiousness on Organizational Citizenship Behavior: The Mediating Role of Digital Self-Efficacy among University Lecturers - Aprilia Maharani Ayuningsih; Wahyu Rahardjo; Maizar Saputra; Indria Hapsari; Ratna Maharani Hapsari (Asosiasi Dosen Muda Indonesia, 2026)
Organizational citizenship behavior (OCB) is increasingly important in higher education because lecturers are expected to contribute beyond their formal duties while adapting to digital transformation. This study examines whether digital self-efficacy mediates the effect of conscientiousness on organizational citizenship behavior among university lecturers. Methodology: This study employed a quantitative cross-sectional design involving 112 lecturers in Jakarta selected through convenience sampling. Data were collected using an online questionnaire distributed through Google Forms and analyzed using correlation and path analysis with JASP software. Findings: Conscientiousness positively influenced both digital self-efficacy and organizational citizenship behavior. Digital self-efficacy also positively affected organizational citizenship behavior. However, the indirect effect of conscientiousness on organizational citizenship behavior through digital self-efficacy was weaker than its direct effect. Therefore, digital self-efficacy did not significantly mediate the relationship between conscientiousness and organizational citizenship behavior. Implications: The findings indicate that lecturers’ voluntary contributions are more strongly influenced by stable personality traits, professional responsibility, and commitment to academic roles than by confidence in using digital technology. Higher education institutions should therefore strengthen professional values, collaborative culture, and recognition of lecturers’ extra-role contributions while continuing to support digital competency development. Originality: This study integrates conscientiousness, digital self-efficacy, and organizational citizenship behavior within a single empirical model and demonstrates that digital self-efficacy is not the primary psychological mechanism connecting conscientiousness with OCB among lecturers.